Engineering the Mechanical Stability of a Therapeutic Complex between Affibody and Programmed Death-Ligand 1 by Anchor Point Selection - Yang, Byeongseon; Gomes, Diego E. B.; Liu, Zhaowei; Santos, Mariana Sá; Li, Jiajun; Bernardi, Rafael C.; Nash, Michael A. (ACS nano, 2024)
Protein–protein complexes can vary in mechanical stability depending on the direction from which force is applied. Here, we investigated the mechanical stability of a complex between a binding scaffold called Affibody and an immune checkpoint protein Programmed Death-Ligand 1 (PD-L1). We used AFM single-molecule force spectroscopy with bioorthogonal clickable peptide handles, shear stress bead adhesion assays, molecular modeling, and steered molecular dynamics (SMD) to understand the pulling point dependency of the mechanostability of the Affibody:(PD-L1) complex. We observed a wide range of rupture forces depending on the anchor point. Pulling from residue #22 on Affibody generated an intermediate state attributed to partially unfolded PD-L1, while pulling from Affibody’s N-terminus generated a force-activated catch bond. Pulling from residue #22 or #47 on Affibody generated high rupture forces, with the complex breaking at up to ∼190 pN under loading rates of ∼104–105 pN/s, representing a ∼4-fold increase as compared with low-force N-terminal pulling. SMD simulations showed relative tendencies in rupture forces that were consistent with experiments and, through visualization of force propagation networks, provided mechanistic insights. These results demonstrate how the mechanical properties of protein–protein interfaces can be controlled by informed choice of site-specific bioconjugation points within molecules, with implications for optimal bioconjugation strategies in drug delivery vehicles.